Empowering Change: Addressing the Roots of intergenerational Prostitution in India - Magotra, Aashima; Ranjan, Rajesh; Verma, Suman; Kathuria, Bhawna (Indian Journal of Community Health, 2025)
Intergenerational caste-based prostitution remains a critical social and public health issue in India. Marginalized communities continue to face systemic exploitation due to socio-economic deprivation, caste-based discrimination, and entrenched cultural practices. Aims & Objectives: The objective of this review is to examine the historical, socio-cultural, and economic factors sustaining intergenerational prostitution in India, to explore its impact on marginalized communities, and to identify potential solutions and public health interventions for meaningful social transformation. Methodology: A narrative review was conducted using PubMed, Scopus, Google Scholar, government reports, NGO publications, and policy documents. Literature addressing caste-linked prostitution, socio-economic drivers, and rehabilitation strategies was included. Data were thematically synthesized under categories such as historical marginalization, policy gaps, and intervention strategies. Results: Findings highlight that communities like the Bedia, Perna, Nat, and Banchhada remain trapped in prostitution due to historical oppression, poverty, and lack of education. Colonial-era laws such as the Criminal Tribes Act and practices like the Devadasi system reinforced the cycle. Stigma, health risks, and gender inequality exacerbate vulnerability. Conclusion: Breaking the intergenerational cycle requires a multi-level approach involving legal reforms, access to education, economic empowerment, and community-based interventions to restore dignity and reduce exploitation.